1975
DOI: 10.1007/bf00010015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of potassium nutrition on tomato plant growth and fruit development

Abstract: The effect of K nutrition on the growth in sand culture of young tomato plants, cv. Amberley Cross, was examined and the concentrations of K in the nutrient feed and in the leaves associated with maximum flower number, fruit set and yield were determined. The distribution of K between and within fruit trusses of normal and K-deficient plants, cv. Amberley Cross and Moneymaker grown in peat/loam was also studied. Total dry weights of 6-wk-old plants grown in sand were maximal when the nutrient feed contained 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
3
2

Year Published

1975
1975
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 25 publications
0
34
3
2
Order By: Relevance
“…When potassium uptake is lower than demand, foliar potassium is mobilized to the fruit, which is detrimental for plant growth and fruit set and quality (Besford and Maw, 1975). Pre-harvest sprays of potassium and growth regulators are one of the most important practices of the new strategies applied in the integrated fruit production systems, improving fruit quality (Mandal et al, 2012).…”
Section: Issn: 2319-7706 Volume 6 Number 5 (2017) Pp 1337-1343mentioning
confidence: 99%
“…When potassium uptake is lower than demand, foliar potassium is mobilized to the fruit, which is detrimental for plant growth and fruit set and quality (Besford and Maw, 1975). Pre-harvest sprays of potassium and growth regulators are one of the most important practices of the new strategies applied in the integrated fruit production systems, improving fruit quality (Mandal et al, 2012).…”
Section: Issn: 2319-7706 Volume 6 Number 5 (2017) Pp 1337-1343mentioning
confidence: 99%
“…46,47 Voogt and Sonneveld 48 found that with increases in tomato plant growth, potassium absorption increases to a relatively greater extent than that of other nutrients. In other studies, it was found that potassium requirement of greenhouse tomatoes is high for vegetative growth, 49,50 fruit production, 51 and fruit quality. 52,53 Lower potassium levels in the culture solution may limit its assimilation into plant parts and retard plant growth, flower development, and fruit set.…”
Section: Potassium As Major Plant Nutritionmentioning
confidence: 88%
“…52,53 Lower potassium levels in the culture solution may limit its assimilation into plant parts and retard plant growth, flower development, and fruit set. 51 It has direct effects on the partitioning of dry matter to the fruits and roots, and the growth of these organs is inhibited at lower potassium 54 and also fruit quality. 52,55 During the reproductive growth periods, fruits are the strongest sink for both carbon assimilates and potassium, therefore, quantitative management potassium in the culture solution is important option for producing low potassium fruits.…”
Section: Potassium As Major Plant Nutritionmentioning
confidence: 99%
“…Low yield of tomato may be attributed to several factors such as nutritional deficiencies, pest and disease attack, inadequate irrigation, incorrect time of planting etc. Improvement in tomato yield with the application of N, P, K fertilizers has been reported by Besford and Maw (1975), Adams et al (1978), Asi and Amjad (1985) and Maynard (1994). The present study was under taken to determine the effect of NPK on tomato plants by using them independently under normal field conditions.…”
Section: Introductionmentioning
confidence: 92%